Answer:
x = 5
y = 4
Step-by-step explanation:
1. 2x + 2y = 18
2. x + 3y = 17
Multiply the first equation by 1 and the second equation by 2 to eliminate x
We have
2x + 2y = 18
2x + 6y = 34
Subtract equation 2 from equation 1
-4y = -16
Divide both sides by -4 to isolate y
-4y/-4 = -16/-4
y = 4
Now substitute 4 for y in either equation to get x. Using equation 2 we have
x + 3y = 17
x + 3 x 4 = 17
x + 12 = 17
Subtract 12 from both sides
x + 12 - 12 = 17 - 12
x = 5
x = 5 and
y = 4
Answer: y = 4 and x = 1
Step-by-step explanation:
when y is 2, x is 0.5
when y is 4, x is 1
.(+ 2) .(+ 0.5)
.(+ 2) .(+ 0.5)
.(+ 2) .(+ 0.5)
.(+ 2) .(+ 0.5)
the rule is that y is 4 times larger than x
n, n + 2, n + 4, n + 6 - four consecutive odd integers
-72 - the sum
The equation:
n + (n + 2) + (n + 4) + (n + 6) = -72
n + n + 2 + n + 4 + n + 6 = -72
4n + 12 = -72 |subtract 12 from both sides
4n = -84 |divide both sides by 4
n = -21
n + 2 = -21 + 2 = -19
n + 4 = -21 + 4 = -17
n + 6 = -21 + 6 = -15
Answer: -21, -19, -17, -15.
Answer:
a
Step-by-step explanation: